Intelligent optimization algorithm based on benchmarking - Anshi XIE (Dianxin kexue)
Many of the issues in scientific research,engineeringand management can be transformed into optimization problems.The various methods applied to these problems were a variety of models.Designing different methods was designing different models.The theme was to model the benchmarking philosophy in business management as a meta-heuristic search method for single objective bound-constrained real-parameter optimization problems.According to the principle of Occam’s Razor,many complicated operators and their probability tuning rules were abandoned and a simple framework was used to organize the core operators to achieve the effect of many composition algorithms.